Consumption of Calcium and Knowledge About Calcium Sources and Nutrition Labels Among Lower Secondary School Students in Thailand - Jaisaard R; Kanjanarach T; Chanaboon S; Ban B (Dove Medical Press, 2021)
Raksaworn Jaisaard,1 Tipaporn Kanjanarach,2 Sutin Chanaboon,3 Borey Ban4 1Pharmacy and Health System Graduate Program, Faculty of Pharmaceutical Sciences, Khon Kaen University, Khon Kaen, 40002, Thailand; 2Department of Social and Administrative Pharmacy and Center for Research and Development of Herbal Health Product, Faculty of Pharmaceutical Sciences, Khon Kaen University, Khon Kaen, 40002, Thailand; 3Department of Community Health, Sirindhorn College of Public Health Khon Kaen, Khon Kaen, 40000, Thailand; 4Technical School for Medical Care, University of Health Sciences, Phnom Penh, CambodiaCorrespondence: Tipaporn KanjanarachDepartment of Social and Administrative Pharmacy and Center for Research and Development of Herbal Health Product, Faculty of Pharmaceutical Sciences, Khon Kaen University, 123 Moo 16, Mittraphap Road, Nai Mueang Subdistrict, Mueang District, Khon Kaen, 40002, ThailandTel +66 81 739 2822Fax +66 043 202 379Email otipkan@kku.ac.thBorey BanTechnical School for Medical Care, University of Health Sciences, Phnom Penh, CambodiaTel +855 17 436 496Email boreyban89@gmail.comObjective: A three study research program was conducted to identify high calcium products available in the market (study I), identify high calcium products that were known or consumed by lower secondary school students in the last three months (study II), and identify the amount and sources of calcium that students had consumed in the prior 24 hours, their knowledge about sources of high calcium and how to interpret calcium information on nutrition labels of food packages (study III).Methods: In study I, a cross-sectional market survey was employed. In studies II and III, a school-based cross-sectional survey was employed. The survey population was students enrolled in grades 7- 9 (11- 14 years old) in a medium-sized lower secondary school in semi-urban Khon Kaen, Thailand. A total of 309 students were invited, with 168 and 209 students participating in studies II and III, respectively. Data were collected with self-administered questionnaires.Results: Ninety-three high calcium products were identified. Only 49 were known or consumed by students in the last three months. The median amount of calcium consumed in the previous 24 hours was 410 mg (IQR: 160, 983). Only 31.1% of students (65/209) consumed more than the Thai recommended daily intake (TRDI) of calcium (800mg) in the previous 24 hours. Their main source of calcium was milk. Other high calcium items that were consumed were malt drink, minnow, canned fish, calcium fortified soy milk and Chinese kale. The overall average knowledge score was 6.5± 2.4 out of a maximum of 17. The average knowledge scores for high calcium food sources and for interpreting the calcium information on a sample nutrition label were 4.6+1.8 (out of 12), and 1.9± 1.2 (out of 5), respectively.Discussion: Students should be introduced to high calcium products in their community such as hard tofu, minnow, and small freshwater shrimp. Educational programs on nutrition label interpretation are needed.Keywords: calcium intake, adolescent, calcium-rich food, calcium knowledge, source of calcium, nutrition fact